Volume Ekspor Komoditas Pisang Indonesia Periode 1989-2013 dan Faktor-Faktor yang Mempengaruhi - Saputro, Kukuh Dwi; Mustika, Made Dwi Setyadhi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 8, Agustus 2015 (pp. 873-1047), 2015)
Indonesia's export growth also supported by the agricultural sector, one of which is a commodity bananas. including banana export commodities that are important in the field of horticulture and has existed since long been a commodity trading has an international reputation. The purpose of this study was to determine the development of the banana commodity export volume and variables that can affect the volume of commodity exports bananas Indonesia period 1989-2013. Data was processed using descriptive analysis, multiple linear regression analysis and standardized coefficient beta. Results of analysis explains that the simultaneous exchange rate of the rupiah against the US dollar, inflation, production and harvested area significantly influence the volume of commodity exports Indonesia 1989 - 2013. The rupiah against the US dollar partially significant negative effect, whereas inflation, production and harvested area effect Positive significantly to the volume of commodity exports bananas Indonesia period 1989 - 2013. The harvested area is a variable that has a dominant influence on the volume of commodity exports banana in Indonesia.
Keywords: Ekspor Komoditas Pisang; Kurs Rupiah Terhadap Dollar Amerika Serikat; Inflasi; Produksi; Luas Panen